Lia wants to estimate 4 1/7 x 3 3/5 To estimate, she simplifies the expression 4 x 3 1/2 .Is Lia’s estimate a close estimate, an underestimate, or an overestimate?

A.underestimate

B.overestimate

C.close estimate

Answers

Answer 1
Answer: Given:
4 1/7 * 3 3/5

4 1/7 = (4*7)+1/7 = 29/7
3 3/5 = (3*5)+3/5 = 18/5

29/7 * 18/5 = 29 * 18 / 7 * 5 = 522 / 35 = 14.91

Simplified expression.
4 x 3 1/2

3 1/2 = (3*2)+1/2 = 7/2

4 * 7/2 = 4*7 / 2 = 28 / 2 = 14

It is a close estimate.   Actual: 14.91 vs Estimate: 14

Related Questions

Frank swims laps during swim practice. His coach tells him to swim a certain number of meters (total) each week. Here's a formula for this scenario:n=t/p t= total number of meters p= length of a lap (in meters) n= number of laps frank swims Rewrite the formula to determine the length of a lap
Work out 25% of 20 metres
The value of 7 is 200 percent of what number?
Find the coordinates of the midpoint of a segment with the endpoints (16,5) & (28, -13)
Help for branliestFind h.9 fth = [?] ft

Complete the remainder of thetable for the given function rule:
y = -2x +9
-4 -2 0 2 4
[?] [] [] []
y 17

Answers

The complete table of values for the function rule y = -2x +9 is

x -4 -2   0  2  4

y 17    13  9 5  1

What are linear equations?

Linear equations are equations that have constant average rates of change, slope or gradient

How to complete the remainder of the table for the given function rule?

From the question, the function rule is given as:

y = -2x +9

The table of values is given as:

x -4 -2 0 2 4

y 17

Next, we substitute the other values of x in the equation y = -2x +9

y = -2(-2) +9 = 13

y = -2(0) +9 = 9

y = -2(2) +9 = 5

y = -2(4) +9 = 1

So, the complete table of values is

-4     -2   0  2  4

y 17    13  9 5  1

Read more about linear functions at:

brainly.com/question/4025726

#SPJ1

EASY MATH QUESTION PLEASE I NEED HELP! ​

Answers

Answer:

x=8/3

Step by step

determine the defined range

remove parentheses

move the terms

collect like terms and calculate

divide both sides

Simplify the following expression. 4a^-2b

A.) b/4a^2
B.)4b/a^2
C.)1/4a^b2

Answers

ANSWER

The correct answer is B

\frac{4b}{ {a}^(2) }


EXPLANATION

The given exponential expression is

4 {a}^( - 2) b

We can rewrite this as,

4b *  {a}^( - 2)

We need to simplify to obtain a positive index, so we apply the following property,


{a}^( - m)  =  \frac{1}{ {a}^(m) }

This implies that,


4b *  {a}^( - 2)  = 4b *  \frac{1}{ {a}^(2) }

This will finally simplify to,

4b *  {a}^( - 2)  =\frac{4b}{ {a}^(2) }


Therefore the correct answer is B

Answer:

B.)4b/a^2

Step-by-step explanation:

Calculate 12% simple interest to be paid on a loan of $2000 repaid in 1 1/2 year?

Answers

Answer:

1320

Step-by-step explanation:

as

SI=(P×T×R)/100

SI=(2000×12×11/2)/100

SI=132000/100

:.SI=1320

Answer:1320

Step-by-step explanation:2000×12×11/2/100

Two divide by twelve=6

2000÷100=20

20×6×11=1320

3) Solve this system of linear equations by elimination.y=x-1
2x-y=0

*x=-1,y=-2
*x=1,y=2
*x=2,y=1
*x=-2,y=-1

Answers

Answer:

Solving this system of linear equations by elimination we get x=-1 and y=-2

Option 1 is correct option.

Step-by-step explanation:

We are given equations:

y=x-1---eq(1)\n2x-y=0---eq(2)

We need to solve by Elimination method.

Elimination method: Add or subtract the equations to get an equation in one variable.

Rearranging the equation 1 we get

-x+y=-1---eq(1)\n2x-y=0---eq(2)

Add eq(1) and eq(2)

-x+y=-1\n2x-y=0\n------\nx=-1

So, after eliminating y we get x=-1

Now finding y by putting x in eq(1)

y=x-1\ny=-1-1\ny=-2

We get y=-2

So, solving this system of linear equations by elimination we get x=-1 and y=-2

Option 1 is correct option.

Translate the phrase into a mathematical expression and then evaluate it. Four squared divided by two cubed.

Answers

As an expression, it is 4² ÷ 2³. The answer to the expression is 2.